Análisis mecánico entre un hormigón tradicional y hormigón con adición de ceniza de cáscara de maní - Cáceres Encalada, Jonathan Eduardo (2024)
This study investigates the mechanical behaviour of traditional concrete compared to concrete modified with the addition of peanut shell ash in percentages of 5%, 10%, and 15% as a partial replacement for cement. The purpose is to evaluate the viability of this agricultural by-product as a sustainable material in construction, specifically analysing compressive strength at 7, 14, and 28 days. Physical and mechanical tests were conducted on cured and compressed concrete specimens. The results show that the design strength of traditional concrete is 210 kg/cm². Mixtures with 5% ash presented a slight decrease in strength, between 2-5%, while with 10% the reduction was 5-8%. Using 15% ash, the decrease in strength was more significant, reaching 10-15%. Although the addition of peanut shell ash in low proportions is viable and contributes to sustainability, its use in higher percentages compromises the mechanical strength of the concrete, limiting its application in structures requiring high durability. This study suggests that peanut shell ash can be used in concrete, but further research is recommended to optimize the mixtures to maximize its benefits.